2018
DOI: 10.1182/blood-2018-05-848408
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow–specific loss of ABI1 induces myeloproliferative neoplasm with features resembling human myelofibrosis

Abstract: Abstract Although the pathogenesis of primary myelofibrosis (PMF) and other myeloproliferative neoplasms (MPNs) is linked to constitutive activation of the JAK-STAT pathway, JAK inhibitors have neither curative nor MPN-stem cell-eradicating potential, indicating that other targetable mechanisms are contributing to the pathophysiology of MPNs. We previously demonstrated that Abelson interactor 1 (Abi-1), a negative regulator of Abelson kinase 1, functions as a tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…It has been reported that intracellular delivery of FANA ASOs in multiple cell lines, including CD34 + stem cells, can be accomplished in the absence of delivery agents such as carrier vehicles or molecular conjugations 19, 20. Therefore, we first determined whether FANA ASOs could be internalized into PBMCs without the help of delivery agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that intracellular delivery of FANA ASOs in multiple cell lines, including CD34 + stem cells, can be accomplished in the absence of delivery agents such as carrier vehicles or molecular conjugations 19, 20. Therefore, we first determined whether FANA ASOs could be internalized into PBMCs without the help of delivery agents.…”
Section: Resultsmentioning
confidence: 99%
“…: 19 they showed that PS-modified FANA ASOs are compatible with gymnotic delivery in multiple cell lines and are as effective at inhibiting gene expression as corresponding LNA-modified ASOs. More recently, Chorzalska et al 20 . demonstrated that FANA ASOs gymnotically silenced a target gene (Abi-1) with knockdown efficiency greater than 50% in human CD34 + cells isolated from the bone marrow of healthy donors.…”
Section: Introductionmentioning
confidence: 99%
“…In murine models, loss of Abi-1 induces features similar to myelofibrosis by activation of Src family kinases, STAT3 and NF-kB, suggesting a means for myelofibrosis that is beyond JAK2 activation. 58…”
Section: Jak-stat Signaling and Beyondmentioning
confidence: 99%
“…Reduced ABI-1 gene expression was observed in granulocytes from PMF patients and patients with MF secondary to PV but not in ET, PV, or MF secondary to ET. Hence, Chorzalska et al induced conditional deletion of Abi-1 in mice using the Mx1Cre system [ 63 ] ( Table 2 ). Loss of Abi-1 in the bone marrow of mice resulted in a PMF phenotype featuring leukocytosis, thrombocytosis, anemia, splenomegaly, megakaryocytosis, and fibrosis in the bone marrow.…”
Section: Other Models Of Mfmentioning
confidence: 99%